Sutika Paricharya W.S.R. To Post-Partum Care- A Samhita Based Review - Swati, Sipika (International Research Journal of Ayurveda & Yoga, 2021)
Background: Puerperium is period following childbirth during which all body tissues revert back to approximately a pre- pregnant state. All Ayurvedic treatises have given a detailed account for Sutika paricharya. Sutika kala is a period begins after expulsion of placenta. Maternal mortality and morbidity are most challenging problem of our country. A recent survey by BJOG (2004) in certain villages in India mentions incidence of maternal morbidity as high as 52.6%. Prevalence of Puerperal morbidity is at a whopping rate of 42.9%. Methodology: The study is narrative review of therapeutic principles of Sutika Paricharya in various classical texts of Ayurveda. Relevant chapters from Bruhatrayee and Laghutrayee were reviewed with the relevant commentaries. Modern literature on the therapeutic modalities of Sutika Paricharya also reviewed and compared with the ancient texts. Discussion and Conclusion: This period is of happiness & contentment, on one hand and physical & mental fatigue due to delivery, on the other hand, she become weak or emaciated after loss of blood and body fluid during delivery. Frequent post- partum morbidity and its association with adverse perinatal outcomes suggest the need for better post-partum care in developing country like India for both mother and baby. The regimen that helps the woman to regain her lost vitality and helps her body to revert back to pre- pregnant state is called Sutika paricharya. Ayurvedic post-partum care is based on the therapeutic principles like Garbhashaya shuddhi, Dhatu-paripurnata, sthanya- vriddhi, punar navekarana are well established. A stage of Physical, mental and physiological wellbeing is re-stabilized.